Perancangan Sistem Pendukung Keputusan Dalam Penilaian Kinerja Guru Dan Pegawai Menggunakan Metode Vikor (Studi Kasus : SMP Negeri 1 Kota Tebing Tinggi) - Samuel Manurung; Yoprin H Nainggolan; Yolanda Rumapea (Department of Information Technology, Universitas Timor, Indonesia, 2022)
Having teachers, teaching staff and professional staff is a must for schools in carrying out a quality education process, as is the case with SMP Negeri 1 Kota Tebing Tinggi. For this reason, schools always encourage the improvement of teacher professionalism by monitoring teacher performance in implementing their duties so that they can achieve predetermined competency standards. The creation of a decision support system is one way to assist in determining teacher performance assessments at SMP Negeri 1 Kota Tebing Tinggi and is expected to The system is able to determine the best teacher or employee based on ranking. Decision Support System (DSS) is a system that produces an alternative decision that can be used as a tool in making a decision. The VIKOR method was chosen because this method determines the weight value for each attribute, then proceeds with a ranking process that will select the best alternative from a number of alternatives, in this case the alternative in question is the teacher who has the highest teacher performance assessment (PKG) based on the criteria specified. determined and questionnaires filled out by students and school principals